ICT as a socio-relational medium: a descriptive analysis in the school context with high school adolescents - Espinel-Rubio, Gladys Adriana; Hernández-Suárez, César Augusto; Rojas-Suárez, Jhan Piero (Universidad Pedagógica y Tecnológica de Colombia, 2020)
The purpose of this research was to identify the socio-relational links of the use of ICTs in the adolescent school environment. The research had a mixed approach, with a sample of 40 adolescents, aged 14-17, from grades 9-11 in a Colombian educational institution. The information was collected through the socio-relational mapping, which consisted of graphing the relationships and interactions of the target population, in the virtual and face-to-face environments. The results indicate that the number of relationships that adolescents have in the virtual environment are different from those in the face-to-face environment. This is because there is a greater communicative connectivity. It is concluded that social interactions mediated by ICTs take two forms: the usual connective interaction with the same subjects in the face-to-face environment, and the extended connectivity, which occurs with individuals different from the usual ones.